Regulation of ER stress-induced autophagy by GSK3β-TIP60-ULK1 pathway - Nie, Tiejian (Cell Death Dis, 2016)
Endoplasmic reticulum (ER) stress is involved in many cellular processes. Emerging evidence suggests that ER stress can trigger autophagy; however, the mechanisms by which ER stress regulates autophagy and its role in this condition are not fully understood. HIV Tat-interactive protein, 60 kDa (TIP60) is a newly discovered acetyltransferase that can modulate autophagy flux by activating ULK1 upon growth factor deprivation. In this study, we investigated the mechanisms by which ER stress induces autophagy. We showed that ER stress activates glycogen synthase kinase-3β (GSK3β). This led to a GSK3β-dependent phosphorylation of TIP60, triggering a TIP60-mediated acetylation of ULK1 and activation of autophagy. Inhibition of either GSK3β or TIP60 acetylation activities significantly attenuated ER stress-induced autophagy. Moreover, enhancing the level of TIP60 attenuated the level of CHOP after ER stress, and reduced the ER stress-induced cell death. In contrast, expression of TIP60 mutant that could not be phosphorylated by GSK3β exacerbated the generation of CHOP and increased the ER stress-induced cell death. These findings reveal that ER stress engages the GSK3β-TIP60-ULK1 pathway to increase autophagy. Attenuation of this pathway renders cells more sensitive to and increases the toxicity of ER stress.